Eichhornia crassipes (Mart.) Solms: A Comprehensive Review of Its Chemical Composition, Traditional Use, and Value-Added Products - Ben Bakrim, Widad; Ezzariai, Amine; Karouach, Fadoua; Sobeh, Mansour; Kibret, Mulugeta; Hafidi, Mohamed; Kouisni, Lamfeddal; Yasri, Abdelaziz (Frontiers in Pharmacology, 2022)
Eichhornia crassipes (Mart.) Solms, commonly known as water hyacinth, is one of the world’s most invasive aquatic plants of Pontederiaceae family occurring in tropical and subtropical regions of the world. Although, E. crassipes causes significant ecological and socio-economic issues such as a high loss in water resources, it has multipurpose applications since it is famous for many industrial applications such as bioenergy, biofertilizer production, wastewater treatment (absorption of heavy metals), and animal feed. Furthermore, E. crassipes is rich in diverse bioactive secondary metabolites including sterols, alkaloids, phenolics, flavonoids, tannins, and saponins. These secondary metabolites are well-known for a wide array of therapeutic properties. Findings of this review suggest that extracts and some isolated compounds from E. crassipes possess some pharmacological activities including anticancer, antioxidant, anti-inflammatory, antimicrobial, skin whitening, neuro-, hepato-protective activities, among other biological activities such as allelopathic, larvicidal and insecticidal activities. The present review comprehensively summarizes the chemical composition of E. crassipes, reported to date, along with its traditional uses, pharmacological and biological activities.